Evaluation of an enterovirus group-specific anti-VP1 monoclonal antibody, 5-D8/1, in comparison with neutralization and PCR for rapid identification of enteroviruses in cell culture. - Trabelsi, A (1995)
We evaluated the usefulness of a commercially available monoclonal antibody (MAb) directed against a group-specific epitope of the capsid protein VP1 of enteroviruses for the rapid identification of these viruses in cell culture. The MAb was assayed in an indirect immunofluorescence test with cultured cells infected by various serotypes of enterovirus; all 39 serotypes tested, including echoviruses 22 and 23, which are considered atypical enteroviruses, were reactive. The MAb was also tested with 61 strains recovered from clinical specimens inoculated into cell cultures in comparison with seroneutralization with intersecting pools of hyperimmune sera and PCR with primers from the 5' untranslated region of enteroviruses. There was total agreement between the results obtained with the MAb and those obtained by PCR, even for those strains of enteroviruses which were found to be untypeable with polyclonal antisera. These data demonstrate the usefulness of the MAb for rapid identification of enteroviruses in cell culture.